Erdheim–Chester disease (ECD): Case report, clinical and basic investigations, and review of literature. Issue 42 (October 2016) - Adawi, Mohammad; Bisharat, Bishara; Bowirrat, Abdalla
Abstract: Background: Erdheim–Chester disease (ECD) is an uncommon aggressive, multisystem form of non-Langerhans' cell histocytosis, which was firstly reported by Jakob Erdheim and William chester in 1930. The disease pathological features encompass an aberrant multiplication, overproduction and accumulation of white blood cells called histiocytes within multiple tissues and organs. Herein, we present a case of ECD owing to the rarity of this disease (roughly 550 cases have been described in the literature to date). Methods: We discussed the clinical course, diagnostic evaluations, and the possible treatments. Our case was encountered in an Arab male in his 30's who has suffered from an ongoing bones pain for years. Results: At our rheumatologic department we compiled his recent medical history, which consisted of diagnosis of central diabetes insipidus, hyperprolactinemia and secondary hypogonadism along with the previously conducted laboratory evaluations and imaging which brought to our mind the possibility of an infiltrative disease such as ECD. The diagnosis of ECD was done based on the combinations of pathognomonic radiographic osteosclerosis, neuroimaging, bones biopsies along with a careful clinical evaluation. Given the protean clinical manifestations, interferon-α was considered as our first line treatment of ECD, consequently our patient improved noticeably. Conclusion: Clinical presentation, imaging studies, distinctive pathological findings, followed by bone biopsy showed a non-Langerhans cell histiocytosis, supported by immunohistochemistry exams are essential for the diagnosis. Radiation therapy and Bisphosphonates in addition to cladribine, anakinra, infliximab and vemurafenib (BRAF Inhibitors) are currently advocated as promising second line treatment for patients whose response to interferon-α is unsatisfactory.